Ethics and integrity in research with children and young people - Spencer, Grace (Advances in research ethics and integrity ;, 2021)
The rapid expansion of research with children and young people has compelled researchers to engage carefully and critically with the ethical aspects of their research, including considering the best ways to ensure children's meaningful participation in research in ethically sensitive ways. This international and multi-disciplinary edited collection unpacks some of the ethical complexities of conducting research with children and young people. The chapters in the volume offer an applied perspective to navigating contemporary and complicated ethical issues that can arise in the field of childhood and youth-centred research. The volume moves beyond a focus on standard, procedural research ethics processes and principles to expose some of the situated ethical moments that researchers grapple with in everyday research practice. Offering a guide for researchers around the importance of developing ethical reflexivity, and the obstacles to achieving it, this volume raises new debates around research ethics while sustaining pragmatic guidance for future research developments that can support children and young people's participation in research.